Temporomandibular Joint Movements during Rigid Bronchoscopy and Laryngoscopy under General Anesthesia and Pre-Post Intervention Comparisons - Heinrich D Becker; Karl-Ludwig Sattler; Rudolf Slavicek (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Recently rigid bronchoscopy with metal tubes has gained increasing importance, namely for interventional procedures. The objective was to examine condyle movement during rigid bronchoscopy under general anesthesia. A method to record the tracings was developed using the CADIAX III system (GAMMA AG, Klosterneuburg, Austria). The purpose of our efforts was to find out whether rigid bronchoscopy harms the temporomandibular joint. To this end, we recorded mandible movements before, during and after operation. We also conducted a brief comparison between bronchoscopy and laryngoscopy. The majority of Heidelberg Thoraxklinik patients have a past or present history of lung cancer and as such were under considerable mental stress; this extraordinary mental situation was a factor. Extreme movements were recorded, with motion probably limited by the ligaments. We found no evidence of harm to the temporomandibular joint system.